Pancasila in the Foundation of Legal Education: Various International Comparisons - Razak Mohammaed Hamdani; Poppy Sagita Ramadhani; Sunan Medr Henley (Jurnal Panjar: Pengabdian Bidang Pembelajaran, 2022)
Pancasila as the ideology of the State of Indonesia consists of five principles of sila which are used as guidelines for nation and state in Indonesia. The five precepts are the basis of the Indonesian State that need to be lived out and practiced by all Indonesian citizens, including in the law of nation and state in Indonesia. The State of Indonesia is a rule of law, in order to realize a rule of law, one of them is required a legal instrument that is used to regulate balance and justice in all areas of people's lives and livelihoods through legislation by not ruling out jurisprudential functions. This shows that legislation has an important role in the Indonesian law. Therefore, Indonesia made Pancasila a guideline for nation and state law because Pancasila was in accordance with the personality of the Indonesian nation.